Relationship of Family Support on Adherence to Medication and Recurrence Prevalence in Schizophrenia Patients in Prof. Mental Hospital Dr. Muhammad Ildrem, North Sumatra Province - Kristina; Muslimah Pase (Science Midwifery, 2020)
Schizophrenia is a disease that affects the brain and causes strange and disturbed thoughts, perceptions, emotions, movements, and behavior. The relapse rate in schizophrenia patients is very high because due to non-adherence to taking medication, the family does not pay attention to the patient taking the drug. One way to reduce the recurrence rate in schizophrenic patients is to provide family support. This study aims to determine the relationship between family support regarding adherence to taking medication with the prevalence of recurrence in schizophrenia patients at the Prof. Dr. Muhammad Ildrem, North Sumatra Province. This study used a descriptive correlation type with a cross sectional approach. The total population of the researchers was 311 people. The sampling technique was carried out by using the Accidental sampling technique with 10% of the population so that the sample size was 31 people. Power analysis used the Spearman`s Rho test. The results of the study using the Spearman`s Rho correlation test were obtained p = 0.000 <α 0.05. This shows that there is a relationship between family support and the recurrence rate of schizophrenia patients at Prof. Dr. Mental Hospital. Muhammad Ildrem, North Sumatra Province in 2017. The conclusion is that there is a relationship between family support regarding adherence to taking medication with the prevalence of recurrence of schizophrenia patients in Prof. Dr. Mental Hospital. Muhammad Ildrem, North Sumatra Province. It is hoped that the nurses will pay more attention to the aspects of family support for schizophrenia patients, as well as conduct a home visit when the patient returns. So that when the patient goes home the patient also gets maximum care. family support for schizophrenic patients.